Countdown to partition : - Bhattacharjea, Ajit (HarperCollins Publishers India, 1997)
The book clearly illustrates the ruthless division of India along religious lines grossly undermining the repeated solicitations of Mahatma Gandhi. Lord Mountbatten, designated with most prodigious job of facilitating the transition of powers from the British Royalty to the Indian leaders hurried the whole process impetuously leading to a colossal loss of men and material. Moreover the shoddy demarcation of the international border by Border Commission headed by Radcliffe, a novice to Indian culture, history and landscape exacerbated the damages of partition. The author succinctly outlines all the exalting twists and turns of freedom fighters, Congressmen and Muslim League members. The unprecedented rush and unceremonious decision of dividing the country and fool-hardiness of Congress chieftains was lucidly explained. The author argues that through a calibrated strategy of “speed and acceleration” in transferring powers to India, the British successfully confused Indian leaders. In fact Indian leaders were given just 73 days to sort out administration issues. As a result the unprepared new administration had to bear the brunt of ruthless partition.